2009
DOI: 10.1080/13218710802549456
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Management of Alcohol Use Disorders and Intimate Partner Violence: Community Reinforcement and Family Training

Abstract: Substance use disorders are associated with life-threatening behaviours and substance use is found to strongly trigger criminal behaviour, including intimate partner violence (IPV). Although intimate partners are often subject to aggression and injury, most substance-using offenders refuse to enter formal treatments. Community reinforcement and family training (CRAFT) was developed to help intimate partners to (a) recognize and safely respond to potential violence, (b) improve communication with the substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Parallel to other studies, behavioral factors such as substance abuse and sexual behavior also showed an independent effect on IPV (Roozen, Blaauw, & Meyers, 2009). Sexual intercourse with the partner led to higher risks of sexual IPV victimization.…”
Section: Hypotheses Testingsupporting
confidence: 63%
“…Parallel to other studies, behavioral factors such as substance abuse and sexual behavior also showed an independent effect on IPV (Roozen, Blaauw, & Meyers, 2009). Sexual intercourse with the partner led to higher risks of sexual IPV victimization.…”
Section: Hypotheses Testingsupporting
confidence: 63%
“…The original AA 12 steps facilitative model was meant to last up to 60 days in a residential setting in the hope that a caring and low-stress environment removed from traditional daily life would facilitate the recovery process. This was however extended over the years to between 3 to 6 months ( Roozen, Blaauw. & Meyers, 2009).…”
Section: The Alcoholics Anonymous 12 Steps Facilitation Modelmentioning
confidence: 99%
“…Competencies are not considered innate but must be developed overtime in order to cultivate and improve performance and continue throughout a person's life (Roozen et al, 2009). Competency is also achieved through training and supervision from knowledgeable instructors and supervisors who in this study comprised of addiction counsellors (Kivlahan, 2013).…”
Section: Development Of Social and Personal Competencies In Addictionmentioning
confidence: 99%
“…Evidence for the CRAFT model has generally been positive, and the approach is considered effective relative to other intervention strategies (for reviews of CRAFT, see Meyers et al, 2011; Roozen, Blaauw, & Meyers, 2009; Roozen et al, 2004; Roozen, de Waart, & van der Kroft, 2010). Overall, empirical evidence suggests that the CRAFT model produces favorable outcomes more so than programs that use only one treatment component (Meyers et al, 1999; Szapocznik, Kurtines, Foote, Perez-Vidal, & Hervis, 1986, 1983).…”
Section: Introductionmentioning
confidence: 99%